2016
DOI: 10.1128/aac.01774-15
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriophage Combinations Significantly Reduce Clostridium difficile Growth In Vitro and Proliferation In Vivo

Abstract: The microbiome dysbiosis caused by antibiotic treatment has been associated with both susceptibility to and relapse of Clostridium difficile infection (CDI). Bacteriophage (phage) therapy offers target specificity and dose amplification in situ, but few studies have focused on its use in CDI treatment. This mainly reflects the lack of strictly virulent phages that target this pathogen. While it is widely accepted that temperate phages are unsuitable for therapeutic purposes due to their transduction potential,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
257
0
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 199 publications
(266 citation statements)
references
References 70 publications
(117 reference statements)
8
257
0
1
Order By: Relevance
“…This method was also effectively used in humans to restore resilience against Clostridium difficile colonization. 16,17 A second approach that presents a more structured form of microbiome engineering involves genetically modifying selected microorganisms to provide them new functions that may benefit a host. 7,1820 These methods could include the (i) introduction of new metabolic enzymes that are absent in the host and its microbiome consortia or (ii) incorporation of new small-molecule-generating biosynthetic genes that are responsible for the production of biomolecules not currently made in humans.…”
mentioning
confidence: 99%
“…This method was also effectively used in humans to restore resilience against Clostridium difficile colonization. 16,17 A second approach that presents a more structured form of microbiome engineering involves genetically modifying selected microorganisms to provide them new functions that may benefit a host. 7,1820 These methods could include the (i) introduction of new metabolic enzymes that are absent in the host and its microbiome consortia or (ii) incorporation of new small-molecule-generating biosynthetic genes that are responsible for the production of biomolecules not currently made in humans.…”
mentioning
confidence: 99%
“…Both the genome organisation and particle morphology of CDKM9 and CDKM15 resemble that of the long tailed myoviruses ΦCD27, ΦCD505 and ΦMMP02. Interestingly, however, CDKM9 has the broadest reported host spectrum compared to the reported host ranges of other long tail myoviruses (ΦCD27, ΦCD505, ΦCD508, ΦCDHM2, ΦCDHM4, ΦCDHM5 and ΦCDHM6) as these infected 13% (4/30), 11% (5/47), 4/47, (28%) 22/80, 4/80 (5%), 20/80 (25%), (29%) 23/80 isolates, respectively [6,14,16]. Further, no other long tailed myoviruses have been shown to lyse R027 isolate [6,14,16,60], while siphoviruses infecting R027 strains have been identified [6,16,17] and the only other report in the literature of myoviruses with this ability are the medium myoviruses ΦCD481-1 and ΦCDHM3, both of which caused turbid plaques on a single strain of R027 each [6,16].…”
Section: Discussionmentioning
confidence: 99%
“…The DNA was pelleted by centrifugation at 21,000× g for 20 min and the pellet was washed once with 0.5 mL of 70% ethanol before resuspension in an elution buffer (5 mM TrisCl, pH 8.5). DNA quantity and quality were measured using a Nanodrop 2000 and Qubit Fluorimeter (Thermo Scientific, Loughborough, UK) as described here [6]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…difficile phages has limited research on phage therapy for CDI. A recent study [28] however, showed the potential of phages to treat CDI in a hamster model using combinations of C . difficile phages (a polyvalent cocktail containing between 2 to 5 phages covering a suitable host range was used; the phages delivered to the hamsters were given as simple phage suspensions and bicarbonate was administered to the animals prior to phage delivered orogastrically to reduce the stomach acidity).…”
Section: Introductionmentioning
confidence: 99%